2007
DOI: 10.1080/01411920701434011
|View full text |Cite
|
Sign up to set email alerts
|

Sacrificial girls: a case study of the impact of streaming and setting on gender reform

Abstract: This article reports on research funded by the Australian Research Council to investigate school responses to gender equity. It addresses the efforts of a disadvantaged school to tackle what they perceived to be gender inequalities, but in the process of constructing a top-set and bottom-set/ stream class they are developing new forms of old inequalities and new forms of inequalities. This research indicates that despite popular assertions that girls' education has become the priority of schools and education … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…In seeking to construct an environment that meets the essentialised needs of boys, schools have often taken up projects that reinforce and reinscribe those constructions of masculinity that pose problems for girls in schools (Martino et al 2005); have sacrificed the quality of girls' educational experiences in an attempt to improve boys' outcomes (Charlton et al 2007); and have devalued the achievements of girls (Boaler 1998). The calls for more male teachers also have a negative impact upon female teachers.…”
Section: Contextmentioning
confidence: 98%
“…In seeking to construct an environment that meets the essentialised needs of boys, schools have often taken up projects that reinforce and reinscribe those constructions of masculinity that pose problems for girls in schools (Martino et al 2005); have sacrificed the quality of girls' educational experiences in an attempt to improve boys' outcomes (Charlton et al 2007); and have devalued the achievements of girls (Boaler 1998). The calls for more male teachers also have a negative impact upon female teachers.…”
Section: Contextmentioning
confidence: 98%
“…Research into the effects of so-called tracking in education systems had already shown that highly differentiated educational systems tend to produce more outcome inequality for pupils from different classes and from different ethnic backgrounds (Buchmann & Park, 2009;Charlton, Mills, Martino, & Beckett, 2007;Hillmert & Jacob, 2010;Lynch & Lodge, 2002;Van de Werfhorst & Mijs, 2010). Bedard and Cho (2007) revealed a similar effect for gendered educational choice patterns, namely, that countries with highly differentiated education systems produce more gender inequality than countries with less differentiated systems (Bradley & Charles 2004;Charles, 2011;Van Elk, Van der Steeg, & Webbink, 2009Van Langen, 2007;Van Langen, Rekers-Mombarg, & Dekkers, 2006Wöβmann, 2009).…”
Section: Extent Of Differentiationmentioning
confidence: 99%
“…(p. 228; also see Jones, 2005) Sanford (2006) agrees, stating that schools 'cannot neglect the needs of one group to support the needs of another' (p. 312). In fact, she suggests that differing expectations for girls' and boys' literacy engagement may disadvantage girls (see Charlton, Mills, Martino, & Beckett, 2007). Boys, she argues, through their engagement with multimodal, visual, electronic and digital texts outside of school may in the long run be better equipped for the future.…”
Section: About the Studymentioning
confidence: 94%